Navigation guided removal of a retropharyngeal migrated fish bone into the foramen transversarium - A case report - Praveen R. Iyer; Karthik Ramachandran; Sham Sundar Y; Ajoy Prasad Shetty; Shanmuganathan Rajasekaran (Journal of Orthopaedic Reports)
Background: Fish bone ingestion causing esophageal perforation and retropharyngeal migration is a rare problem presenting to a spine surgeon. Case: A 58-year-old female presented with complaints of odynophagia following ingestion of fish. Rigid laryngoscopy and esophageal endoscopy showed esophageal bulging without any luminal foreign body. X-ray and computed tomography of the neck showed retropharyngeal migration and impaction of the fish bone inside the right foramen transversarium of C3 vertebra. Fish bone was extracted under intra-operative CT navigation through an anterior cervical approach. Conclusion: This report highlights the importance of CT in localizing a migrating retropharyngeal foreign body and navigation aiding in its removal.